2023
DOI: 10.1039/d3ee00841j
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy for perovskite solar cells – drivers, progress and challenges

Rhys G. Charles,
Alex Doolin,
Rodrigo García-Rodríguez
et al.

Abstract: Lead halide perovskite solar cells (PSCs) are an emerging solar photovoltaic (PV) technology on the cusp of commercialisation, promising to deliver the lowest cost solar energy to date (>32 $/MWh)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 287 publications
(483 reference statements)
0
13
0
Order By: Relevance
“…For the LCOE calculation, the initial installation cost I t consists of modules, inverters, other BOS equipment, installation labor, project overhead costs, land fees, transportation, taxes, etc. [57,58,[131][132][133] Light and flexible modules have reduced weight that allows for alternative mounting methods that, for instance, do not require additional racking used for heavy modules but can be placed conformally to the roof (Figure 7g). [131][132][133] This will contribute to a significant reduction in installation labor and racking costs.…”
Section: Cost Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For the LCOE calculation, the initial installation cost I t consists of modules, inverters, other BOS equipment, installation labor, project overhead costs, land fees, transportation, taxes, etc. [57,58,[131][132][133] Light and flexible modules have reduced weight that allows for alternative mounting methods that, for instance, do not require additional racking used for heavy modules but can be placed conformally to the roof (Figure 7g). [131][132][133] This will contribute to a significant reduction in installation labor and racking costs.…”
Section: Cost Analysismentioning
confidence: 99%
“…[57,58,[131][132][133] Light and flexible modules have reduced weight that allows for alternative mounting methods that, for instance, do not require additional racking used for heavy modules but can be placed conformally to the roof (Figure 7g). [131][132][133] This will contribute to a significant reduction in installation labor and racking costs. Metacarpa et al reported up to a 47% cost reduction in hardware installation labor through the change from rigid to flexible PV modules.…”
Section: Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, perovskite solar cells (PSC), a novel PV technology, could be efficiently used for indoor applications. PSCs continue to attract research attention due to their excellent optoelectronic properties and low production costs, resulting in enormous potential both as stand-alone SCs as well as subcells of tandem solar cells. Their high power conversion efficiency (PCE), higher (and tunable) bandgap than c-Si and therefore higher open-circuit voltage make them a potentially attractive option for low-light, energy harvesting applications. ,,, The less harsh conditions of indoor operation compared with field operation mean that indoor PV is a promising niche for perovskite technology. Namely, achieving stability and longevity of PSCs remains one of the most elusive challenges of the technology, as a typical device lifetime is usually measured in days or months instead of years due to sensitivity to temperature and humidity-induced degradation, which are within much less damaging ranges in indoor conditions …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the power conversion efficiency (PCE) of organic–inorganic hybrid perovskite solar cells (PSCs) has experienced rapid advancements, surpassing 26% [ 1 ] and approaching the efficiency levels of the best currently available silicon solar cells [ 1 ]. This underscores the promising application potential of perovskite solar cells [ 2 ]. However, the commercial utilization of pure lead (Pb)-based perovskites is still hindered by their toxicity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%